1993
DOI: 10.1002/j.1552-4604.1993.tb03947.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pretreatment Periods with Diltiazem on Nifedipine Kinetics

Abstract: The effect of durations of diltiazem pretreatment on nifedipine kinetics was evaluated. Eighteen healthy male subjects were randomly allocated to three groups, 6 subjects each, for single doses of 60 mg diltiazem, and 3 days and 6 days with diltiazem 60 mg three times a day. All subjects received 20 mg nifedipine orally on two occasions using a double-blind cross-over, placebo-controlled method. No significant difference on pharmacokinetic parameters of nifedipine without diltiazem were observed among three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Diltiazem is also a mechanism‐based inactivator of CYP3A 6 . Ohashi et al 20 studied the effect of a single dose and multiple doses (4 and 7 days of treatment) of diltiazem on the pharmacokinetics of nifedipine. The study showed that diltiazem increased AUC of nifedipine in a duration‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Diltiazem is also a mechanism‐based inactivator of CYP3A 6 . Ohashi et al 20 studied the effect of a single dose and multiple doses (4 and 7 days of treatment) of diltiazem on the pharmacokinetics of nifedipine. The study showed that diltiazem increased AUC of nifedipine in a duration‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Diltiazem has been reported to affect the pharmacokinetics was increased by about 4 and 3 times, respectively, in comparison with the placebo pretreatment. In our study, of nifedipine depending on the dosage [2], and the period of pretreatment [3]. There was no difference reported the AUC of triazolam was increased by about 2.3 times, and the t 1/2 was prolonged by 1.8 times with diltiazem between 3 days and 6 days of treatment.…”
Section: Pharmacodynamics Analysismentioning
confidence: 80%
“…Diltiazem has been reported to inhibit hepatic enzyme metabolism in combination with many therapeutic agents that are metabolized by the CYP3A Methods isozyme, for example, nifedipine, carbamazepine, propranolol and cyclosporine [1]. Ohashi et al [2,3] showed that the Study design metabolism of nifedipine, a substrate for CYP3A4, was affected by the concomitant use of diltiazem, revealing that Seven healthy male volunteers participated in a randomized, double-blind, three-phase crossover study at intervals of at the effect was dose-dependent and was maintained on a plateau during repeated administration. least 1 week.…”
mentioning
confidence: 99%
“…In in vitro kinetic studies the N ‐desmethyl and N,N ,didesmethyl metabolites of diltiazem are, respectively, 11 and 200 times more potent than the parent drug, as competitive inhibitors of CYP3A4 [ 4]. During chronic therapy these metabolites accumulate in plasma and can reduce the clearance of the parent drug [ 16, 17]. The N ‐demethylated metabolites of diltiazem may possibly contribute to the inhibition of the CYP3A4‐mediated metabolism of simvastatin in vivo.…”
Section: Discussionmentioning
confidence: 99%